2012
DOI: 10.1080/02699931.2011.619520
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellum and processing of negative facial emotions: Cerebellar transcranial DC stimulation specifically enhances the emotional recognition of facial anger and sadness

Abstract: Some evidence suggests that the cerebellum participates in the complex network processing emotional facial expression. To evaluate the role of the cerebellum in recognizing facial expressions we delivered transcranial direct current stimulation (tDCS) over the cerebellum and prefrontal cortex. A facial emotion recognition task was administered to 21 healthy subjects before and after cerebellar tDCS; we also tested subjects with a visual attention task and a visual analogue scale (VAS) for mood. Anodal and cath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
128
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(145 citation statements)
references
References 36 publications
14
128
1
2
Order By: Relevance
“…Cerebellar lesions have been known to be involved in pathological laughter and crying resulting from impaired emotional expression [20]. According to Ferrucci, et al the cerebellum is involved in processing facial expression of negative emotions [21]. Therefore, injury to the cerebellum may result in abnormalities in control of voluntary movements and decrease in living standard of people living with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebellar lesions have been known to be involved in pathological laughter and crying resulting from impaired emotional expression [20]. According to Ferrucci, et al the cerebellum is involved in processing facial expression of negative emotions [21]. Therefore, injury to the cerebellum may result in abnormalities in control of voluntary movements and decrease in living standard of people living with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Direct support of the hypothesis of cerebellar function in the conscious processing of emotional faces comes from stimulation studies that have observed a greater ability to recognize negative facial expressions after transcranial direct current stimulation (tDCS) is performed over the cerebellum [86].…”
Section: Cerebellar Involvement In the Conscious Component Of Emotionsmentioning
confidence: 98%
“…Several reports have identified the cerebellum as recognizing and discriminating emotional facial expressions, in particular for negative emotions (Turner et al, 2007;Fusar-Poli et al, 2009;Ferrucci et al, 2012;Adamaszek et al, 2014). These observations suggest that in addition to its recognized motor tasks, the cerebellum is involved in the integration of emotional responses in social behaviors.…”
Section: Introductionmentioning
confidence: 96%